Controversies and Common Ground in Wild and Domestic Fine Fiber Production in Argentina - von Thungen, Julieta; Martin, Elisa; Lanari, Maria Rosa (Frontiers in Sustainable Food Systems, 2021)
This work analyzes possible obstacles to develop innovative products or old merchandise by a new method. It will look into the actors of fine fiber production and meat in three distinctive socioecological systems. Through three cases we explore how natural resources management connected with interests, values, and knowledge of actors. We use the Sabato-Botana Triangle model to connect actors involved. The vertices of the triangle are a) government, b) knowledge production and c) rural livelihoods. The government vertex is the national and provincial level of authorities that are involved with decision-makers at the national and provincial level. The Scientific-Technological Vertex includes researchers from INTA, CONICET and the Universities. Rural livelihoods will include livestock keepers, farmers, and local actors with traditional knowledge. We will address the goods and services provided by two species of wild camelids and domestic livestock. The three cases have similarities and differences in the focus and common ground of the controversial spaces. They create different networks of relationships and bonds leading to diverse results. Top down or bottom up experiences hold distinct epistemologies and research consequences, they affect rural livelihoods in various ways. For the three rural livelihoods, it is meaningful that regulations should be endogenous social constructions. However, there are no longitudinal studies on the trajectories of these cases. Long-term multispecies grazing opportunities are available for the three cases. It depends on how the vertices of the SBT identify find flexibility in their common ground to face of catastrophic events.